Developing Tourism Performance Dashboard for National Tourism Organisation: The Case of Indonesia - Rezha Soeprawa; Riza Supono (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2024)
The tourism industry represents a significant component of the Indonesian economy, necessitating effective management and monitoring to facilitate the recovery process and ensure sustainable growth. We can construct a thematic dashboard that furnishes real-time insights and visualizations for expeditious data analysis by employing the most recent technological advances. This research examines and develops a conceptual framework for a data structure and infrastructure that is fundamental to the creation of the Tourism Performance Dashboard. The dashboard underscores the significance of the tourism sector in fortifying national economic resilience. To attain this objective, the dashboard monitors six key performance indicators. This study employs a user-centered design approach through document analysis and focus group discussions to identify essential features necessary for the dashboard. The resulting dashboard prototype exemplifies data interoperability and analytical capabilities, which have considerable potential to enhance the management of Indonesia's tourism industry.